2019
DOI: 10.1089/ham.2019.0007
|View full text |Cite
|
Sign up to set email alerts
|

Day of Ascent Dosing of Acetazolamide for Prevention of Acute Mountain Sickness

Abstract: Background: Acetazolamide is the most common medication used for prevention of acute mountain sickness (AMS), usually administered the day or night before ascent. The objective of this study was to evaluate the efficacy of day of ascent dosing of acetazolamide for AMS prevention. Methods: Double-blind, randomized, controlled noninferiority trial of acetazolamide 125 mg twice daily beginning either the night before or the morning of ascent. Healthy low altitude adults ascended from 1240 m (4100 ft) to 3810 m (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
0
14
1
1
Order By: Relevance
“…According to previous arguments,[ 8 21 47 ] we expected to see different treatment effects of acetazolamide with different timing at start of acetazolamide treatment, mode of ascent, timing of AMS assessment, baseline altitude, and endpoint altitude, but these were not demonstrated by our data. Results of meta-regression analysis suggested that the above factors might not have significant influence on the treatment effect of acetazolamide for prevention of AMS.…”
Section: Discussioncontrasting
confidence: 50%
“…According to previous arguments,[ 8 21 47 ] we expected to see different treatment effects of acetazolamide with different timing at start of acetazolamide treatment, mode of ascent, timing of AMS assessment, baseline altitude, and endpoint altitude, but these were not demonstrated by our data. Results of meta-regression analysis suggested that the above factors might not have significant influence on the treatment effect of acetazolamide for prevention of AMS.…”
Section: Discussioncontrasting
confidence: 50%
“…These authors found only a minimally higher incidence of AMS (i.e., 9%) with the day of ascent dosing versus the traditional night before approach. However, AMS severity was less (10%) for the ''day of ascent'' group compared with the ''night before ascent'' group (22%) (Lipman et al, 2019).…”
Section: Resultsmentioning
confidence: 88%
“…Common and early occurring dose-dependent adverse reactions to AZ include peripheral paresthesia (notably a tingling sensation in the hands and feet), increased urination (polyuria), loss of appetite, altered taste, particularly of carbonated beverages, and tinnitus (Simancas-Racines et al, 2018;Sridharan and Sivaramakrishnan, 2018). Less common are nausea, headache, and dizziness, which can unfortunately mimic the symptoms of AMS itself (Williamson et al, 2018) as well as GI distress with AZ (Lipman et al, 2019), and possibly occasional drowsiness and confusion (Simancas-Racines et al, 2018). Moderate, but more rare, events include ocular effects such as myopia (Szawarski and Hall-Thompson, 2009).…”
Section: Adverse Reactions To Azmentioning
confidence: 99%
“… 126 , 132 , 133 Practically, prophylaxis should be initiated 8–24 h before ascent and continued for 48 h up to the highest altitude reached, 134 but administering acetazolamide on the day of ascent was shown to be similarly effective. 135 If staging is used as the primary acclimatization strategy acetazolamide could safely be used in an on-and-off strategy, taking the before mentioned rules into account.…”
Section: How To Prevent High-altitude Illnesses?mentioning
confidence: 99%